PENGARUH SUBSTITUSI TEPUNG KULIT MELINJO (Gnetum gnemon L.) TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK TORTILLA CHIPS TINGGI SERAT - Iswahyudi Iswahyudi; Nenden Apriliyanti; Imas Arumsari (ARGIPA (Arsip Gizi dan Pangan), 2021)
Melinjo peel is a local food ingredient that is easily found in the community and has the potential to be developed into high-fiber snacks. The aim of this research was to produce high-fiber tortilla chips that are chemically and organoleptically acceptable. This study used a completely randomized design (CRD) with one factorial and two replications. Factors in the study were the addition of melinjo peel flour to substitute corn which consisted of 3 levels of F1 (20%), F2 (30%), F3 (40%), and F0 (0%) as a control. The analysis consisted of proximate analysis (moisture content, ash content, protein, fat, carbohydrates), total energy, fiber content and organoleptic tests (hedonic test and hedonic quality) using 50 panelists. Data of proximate test, total energy and fiber content were analyzed using the ANOVA test followed by Duncan's Mutliple Test (95% significance). Data of organoleptic test were analyzed using the Kruskal Wallis test and followed by the Mann Whitney test (95% significance). The results showed that the addition of melinjo peel flour to substitute corn had a significant effect on fiber content (p<0,05), but had no significant effect on moisture content, ash content, protein, fat, carbohydrates and total energy (p>0,05). The results of the organoleptic test showed that the addition of melinjo peel flour to substitute corn had a significant effect on the level of preference for color and aroma as well as on taste quality and color quality (p<0,05). F2 (70%: 30%) is the formula for the selected tortilla chips with the nutritional content in 100 g of the ingredients, namely 413.46 kcal of energy, 84.44 g of carbohydrates, 4.56 g of fat, 8.65 g of protein, and 47.59 g of fiber.